Answer:
The correct answer is c = -8/3.
Explanation:
The first step in solving this problem would be to simplify by combining like terms on the left side of the equation.
6c - 8 - 2c = -16 + c
4c - 8 = -16 + c
Then, we can subtract c from both sides of the equation to get rid of the positive c on the right side of the equation.
4c - c - 8 = -16 + c - c
3c - 8 = -16
Next, we can add 8 to both sides of the equation.
3c - 8 + 8 = -16 + 8
3c = - 8
Then, we can divide both sides of the equation by 3.
c = -8/3
Hope this helps!